MONITORING OF INSECTICIDE RESIDUES IN BRINJAL COLLECTED FROM MARKET OF NOSHERA VIRKAN, PAKISTAN - M. F. Iqbal; U. Maqbool; I. Perveez; M. Farooq; M. R. Asi (Journal of Animal and Plant Sciences, 2009)
Insecticide residues were monitored in brinjal. Samples were collected from different locations of Noshera Virkan District Gujranwala during 2006. Brinjal samples were exhaustively extracted with ethyl acetate, cleaned-up with charcoal column and analyzed with high performance thin layer chromatography (HPTLC). On the basis of extant of inhibition of acetyl cholinesterase enzyme, insecticide residues were detected. The insecticide residues in brinjal samples were calculated on average spot area basis of the standards. Imidacloprid was in the range of 0-0.028 mg/kg, carbofuran 0-0.034 mg/kg and chlorpyriphos 0-0.060 mg/kg. Thus, the residues of imidacloprid and carbofuran were below the maximum residue limits (MRL’s) which was 0.050 mg/kg for carbofuran and chlorpyriphos and 0.230 mg/kg for imidachloprid, respectively except residues of chlorpyriphos. The present research revealed that fresh brinjal samples of the studied area were contaminated and not suitable for consumption by public. It needs special attention due to the hazards of pesticide residues consumed by residents of the study area.
Keywords: Brinjal; insecticide; residues; HPTLC